Molecular cloning, sequencing, and transcriptional analysis of the groESL operon from Bacillus stearothermophilus. - Schön, U (1993)
Using a gene probe of the Bacillus subtilis groEL gene, a 7.3-kb HindIII fragment of chromosomal DNA of Bacillus stearothermophilus was cloned. Sequencing of 2,309 bp led to the detection of two open reading frames in the order groES groEL. Primer extension studies revealed one potential transcription start site preceding the groESL operon, which was activated upon temperature upshift. Northern blot (RNA) analysis resolved two mRNA species with lengths of 2.2 and 1.5 kb; RNA slot-blot experiments revealed an at least 10-fold increase in the amount of specific mRNA from 0 to 7 min postinduction followed by a decrease. The 9-bp inverted repeat characteristic of many gram-positive bacteria was found within the 5' leader region of the mRNA. The groESL operon of B. stearothermophilus could complement E. coli groES(Ts) and groEL(Ts) mutants for growth at high temperature and for propagation of phage lambda.